Konseling Gestalt: Tinjauan Konseptual atas Prinsip, Teknik, dan Relevansinya dalam Praktik Konseling - Rika Wulandari; Amirah Diniaty (Yayasan Literasi Sains Indonesia, 2026)
The mental health inmates is an issue that is often overlooked within Indonesia's correctional system. This group faces layered psychological pressures, including loss of freedom, social stigma, severed family relationships, and anxiety about social acceptance after release. This community service activity aims to provide counseling services based on the Gestalt approach to inmates at a correctional institution (Lapas) in Pekanbaru, Riau., as a concrete effort to support mental health, strengthen self-awareness, and build emotional regulation capacity. The activity was conducted on June 5, 2026, involving 19 participants, using a three-stage method: administration, psychoeducation, and individual one-on-one counseling sessions between student counselors and inmates. Results indicate that the Gestalt approach effectively facilitated participants' self-awareness of previously unprocessed emotional experiences, encouraged re-authoring of life narratives from stigma toward dignified acceptance, and identified internal strengths rooted in family support and spirituality as foundations of resilience. These findings affirm the relevance of Gestalt counseling as a responsive and dignified psychological intervention for incarcerated populations, while opening space for the development of similar programs on a sustained basis within Indonesian correctional settings.